Human factors study of performance shaping factors associated with shortcut keys in wimp user interface - Tan, Chee Keong. (2008)
This project examined the usage of shortcut keys by the general working population to validate their needs for shortcut keys in today’s WIMP user interfaces. It also investigated the reasons why shortcut keys were infrequently used with respect to key attributes and user perceptions.